Interactions of beta-blockers with model lipid membranes: molecular view of the interaction of acebutolol, oxprenolol, and propranolol with phosphatidylcholine vesicles by time-dependent fluorescence shift and molecular dynamics simulations - Först, Gesche; Cwiklik, Lukasz; Jurkiewicz, Piotr; Schubert, Rolf; Hof, Martin (European journal of pharmaceutics and biopharmaceutics, 2014)
Since pharmacokinetic and pharmacodynamic activities of drugs are often related to their interactions with biomembranes, it is of high interest to establish an approach for the characterization of these interactions at the molecular level. For the present study, beta-blockers (oxprenolol, propranolol, and acebutolol) were selected due to their well described nonspecific membrane effects (NME). Their interactions with model lipid membranes composed of palmitoyloleoylphosphatidylcholine (POPC) were studied using Time-Dependent Fluorescence Shift (TDFS) and Generalized Polarization (GP) as well as molecular dynamics (MD) simulations. Liposomal vesicles were labeled with fluorescent membrane polarity probes (Laurdan, Prodan, and Dtmac). Increasing beta-blocker concentrations (0-10 mM for acebutolol and oxprenolol, and 0-1.5 mM for propranolol) significantly rigidifies the lipid bilayer at the glycerol and headgroup level, which was detected in the steady-state and in the time-resolved fluorescence data. The effects of propranolol were considerably stronger than those of the two other beta-blockers. The addition of fluorescent probes precisely located at different levels within the lipid bilayer revealed the insertion of the beta-blockers into the POPC bilayer at the glycerol backbone level, which was further confirmed by MD simulations in the case of propranolol.
Keywords: Adrenergic beta-Antagonists; Drug-membrane interactions; acebutolol; Lipid Bilayers; Fluorescent Dyes; simulace molekulární dynamiky; Acebutolol; Phosphatidylcholines; Liposomes; Prodan; Molecular Dynamics Simulation; lipidové dvojvrstvy; Glycerol; Oxprenolol; beta blokátory; glycerol; Generalized polarization; Solvent relaxation; Membrane Lipids; Fluorescence; Propranolol; liposomy; Laurdan; oxprenolol; Dtmac; Lipid hydration; NME; fluorescenční barviva; propranolol; fosfatidylcholiny; membránové lipidy; MD; fluorescence